Levels and water soluble organic carbon of atmospheric nanoparticles in a location of Ha Noi, Viet Nam - Thuy, Nguyen Thi Thu; Dung, Nghiem Trung; Sekiguchi, Kazuhiko; Yamaguchi, Ryosuke; Thuy, Ly Bich; Hien, Nguyen Thi Thu (Vietnam Journal of Science and Technology, 2017)
Atmospheric nanoparticles (NPs or PM0.1) were investigated at a site inside the campus of Ha Noi University of Science and Technology (HUST) in Ha Noi, Viet Nam. The sampling was conducted during a rainy season (August, 2015) and a dry season (October to December, 2015). Mass was weighed by an electronic micro-balance, Sartorius ME2, 10-6 g. Number concentrations were measured by an electrical mobility spectrometer (NanoScan, SMPS TSI Model 3910). Water soluble organic carbon (WSOC) was analyzed by a total carbon analyzer (TOC-VCHP, Shimazu). The correlations between WSOC and other components were studied to primarily identify the sources of atmospheric nanoparticles. Secondary organic carbon (SOA) was estimated using elemental carbon (EC) – tracer method. Selected characteristics of nanoparticles including mass concentrations, number concentrations, and WSOC were determined.